ジッケン ヨウ ナンキョク ホーバークラフト - 村尾, 麟一; ムラオ, リンイチ; 森脇, 喜一; モリワキ, キイチ; 村越, 望; ムラコシ, ノゾミ; 大門, 康祐; ダイモン, ヤススケ; 稲葉, 稔; イナバ, ミノル; Murao, Rinichi; Moriwaki, Kiichi; et al. (1985)
P(論文) 南極観測事業におけるホーバークラフトの有用性・適応性に関し, 南極用実用艇建造のための技術データを得ることを目的として, 実験用小型ホーバークラフトが開発建造された。ホーバークラフトは重量2.8tの周辺スカート圧力室型で, 揚力ファンより分岐されたダクト中に装備された方向舵とパフポートによって操縦される。艇は1981年に昭和基地に自力搬入され, 1981から1982年にかけて33時間の走行試験と氷状調査が実施された。計画最高速力55km/hが達成されたが, 走行中エンジンエアクリーナーへの雪の目詰まり, 駐機中ファン空気吹き出し部の凍結などのトラブルが経験された。実験用南極ホーバークラフトの計画, 設計, 主要目, 登坂推進性能, 走行試験の経過と結果が記述されている。 An experimental hovercraft has been developed for tests on the utility, adaptability and operation of hovercraft in the environment of the Antarctic. The Hovercraft Subcommittee formed in 1978 has been managing the planning of this project. The craft is a 2.8t plenum chamber type hovercraft with 60cm depth flexible skirts, fitted to its perimeter. Two rudders equipped within the air jet bleeded from the lift fan, and two puff ports which control the air jet, provide directional control. In order to estimate the performance of the craft, the static thrusts were measured. In January 1981,the craft was unloaded on the fast ice about 40km NW of Syowa Station in the Antarctic. After 3.5 hours run it reached the station, crossing small cracks and puddles. During the summer and winter seasons of 1981/82,33 hours test running and sea-ice survey have been carried out. Some troubles such as the clogging of snow in the engine room, icing on the air outlet from fan scroll and tear of skirts were experienced. The process of planning, design, principal particulars, slope ascending capability and the operation in the Antarctic of the experimental hovercraft are described. departmental bulletin paper